Strategy For Improving Taxpayer Compliance Motorized Vehicles: (Case Study Of SAMSAT Grobogan Regency) - Farida Aulia Rohmah; Karsinah, Karsinah (Jurnal Ekonomi, 2024)
The increasing volume of vehicles should have great potential for motor vehicle tax revenue in Grobogan Regency. SAMSAT has set motor vehicle tax targets in accordance with regional potential, but the realization is still not optimal. This investigate points to decide and analyze the viability and development rate of engine vehicle assess income from the One-Stop Single Organization Framework (SAMSAT) of Grobogan Rule in 2018-2023, analyze the deterrents confronted in expanding engine vehicle citizen compliance in Grobogan Rule, analyze approach procedures for progressing engine vehicle citizen compliance in Grobogan Rule which can be taken by the territorial government to extend engine vehicle citizen compliance. The secondary data came from the Grobogan Regency Statistics Center (BPS) and Samsat report data. Primary data is a way of collecting data using survey research methods so that data is obtained from respondents using direct interview techniques and questionnaires, quantitative methods with a descriptive approach to hierarchical process analysis. The research results show that the performance in achieving PKB targets in Grobogan Regency experienced fluctuations during 2018-2023. Meanwhile, the growth rate of target achievement experienced significant volatility during 2018-2023. In 2023, the growth rate will experience a significant decline and show performance that is not successful in achieving targets. From the policy priority results obtained, it is hoped that policymakers will focus more on the highest weighting criteria, namely "Policy Providing various payment facilities such as online payments or collaborating with retail outlets" compared to other policies, but this does not mean that other policies are unimportant, because every The policy taken by the government will still have an impact, both positive and negative.